2015
DOI: 10.1111/dme.12805
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 diabetes is not associated with an increased prevalence of hepatic steatosis

Abstract: Our data showed that Type 1 diabetes was not associated with an increased prevalence of steatosis. Moreover, our study provided no specific arguments concerning a link between liver fat content and diabetic complications in patients with Type 1 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
34
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 17 publications
5
34
2
2
Order By: Relevance
“…6 In contrast, a magnetic resonance imaging (MRI) study reported a prevalence of only 4.7%. 7 The latter finding is consistent with a smaller MRI study showing lower LFC in T1D patients than in age-and body mass index (BMI)-matched healthy subjects. 8 The aim of this investigation was to assess the prevalence and clinical phenotype of NAFLD in patients with T1D and T2D.…”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations
“…6 In contrast, a magnetic resonance imaging (MRI) study reported a prevalence of only 4.7%. 7 The latter finding is consistent with a smaller MRI study showing lower LFC in T1D patients than in age-and body mass index (BMI)-matched healthy subjects. 8 The aim of this investigation was to assess the prevalence and clinical phenotype of NAFLD in patients with T1D and T2D.…”
Section: Introductionsupporting
confidence: 87%
“…However, ultrasound is significantly less accurate than magnetic resonance spectroscopy for the diagnosis of NAFLD . Another study using MRI reported a prevalence of NAFLD in T1D patients (4.7%) similar to that observed in our study, supporting the conclusion that the prevalence of NAFLD in T1D patients is low. Although NAFLD in T1D patients is not well‐studied, an observational survey reported that T1D patients with elevated liver enzymes had a less favourable cardiovascular risk profile and poorer glycaemic control …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of NAFLD in the present study, performed on a cohort of middle-aged Mediterranean T1D subjects, was intermediate compared with prevalence reported in previous studies. [14][15][16]18 In the present cohort, NAFLD was also associated with Grade 2 overweight, higher TG concentrations, and a higher proportion of statin treatment. Statistical analysis suggested that the presence of NAFLD was associated with higher CIMT, which indicates that systematic screening for NAFLD in T1D may be useful for the identification of subjects at risk not only for further hepatic disease, but also subclinical CVD.…”
Section: Discussionsupporting
confidence: 49%
“…Nevertheless, other studies have found a lower prevalence, not higher than 10%. 17,18 The high prevalence of NAFLD in T1D could be explained by the growing coexistence of MS and T1D, so-called "double diabetes," 19 which is related to intensive insulin treatment and the increase in obesity in T1D subjects, as in the general population. 20 The presence of NAFLD in T1D appears to be independently associated with macrovascular 15 and microvascular chronic complications.…”
Section: Introductionmentioning
confidence: 99%